Efektivitas Penegakan Hukum Tindak Pidana Kekerasan Dalam Rumah Tangga Di Kabupaten Bulukumba - Setiawan, Muh. Yusran; Thalib, Hambali; Razak, Askari (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the effectiveness of law enforcement in domestic violence crimes and the factors influencing law enforcement in such cases. The type of research used is empirical legal research, which focuses on the collection and analysis of data obtained from the real world to assess the effectiveness of law enforcement in domestic violence crimes, as well as direct interviews with law enforcement officers entrusted by law, particularly at the Bulukumba District Court. The results of these interviews will be systematically organized and analyzed accordingly. The research findings indicate that (1) The effectiveness of law enforcement in domestic violence crimes in Bulukumba Regency is still not very effective in its implementation. Not all reports are followed up with formal legal action; instead, the court often attempts mediation between the victim and the perpetrator while providing legal counseling to prevent further instances of domestic violence. Several factors contribute to the ineffectiveness of law enforcement, including the difficulty in proving the crime due to a lack of evidence, the insufficient number of investigators in relation to the number of cases, legal facilities, and the lack of legal awareness among the public regarding domestic violence crimes. (2) The factors influencing the law enforcement of domestic violence crimes in Bulukumba Regency include a lack of reports from domestic violence victims, issues with proving the crime, the position of women in society, the lack of gender sensitivity among law enforcement officers, and the regulations regarding complaint-based crimes. Keywords: law enforcement, domestic violence, factors.